Safety Assessment of Proton-Pump Inhibitors: Study of Cardiovascular Adverse Events Using Global Pharmacovigilance Data - Salma Nur Azizah Azzahra; Fita Rahmawati; Agung Endro Nugroho (Universitas Sebelas Maret, 2026)
Proton-pump inhibitors (PPIs) have been associated with adverse cardiovascular events, underscoring the need for comprehensive safety evaluation, yet systematic consolidation of data on PPI-related adverse drug reactions (ADRs) leading to cardiovascular events remains lacking. This study aims to descriptively analyze cardiovascular events related to PPI use to summarize their safety profile. A quantitative descriptive analysis was performed on cardiovascular ADRs associated with PPIs using global pharmacovigilance data. The top 25 reported cardiovascular ADRs for each PPI were identified from VigiAccess launched by World Health Organization (WHO) global database. We selected the same 20 set potential ADRs using Venny 2.1.0 to enhance the comparability of data and we summarized by frequency and percentage. A total of 15,263 cardiovascular ADR cases were identified. Omeprazole showed the highest reports, mainly palpitations (1,675 cases; 28.5%), cardiac flutter (759 cases; 12.91%), tachycardia (549 cases; 9.34%), and myocardial infarction (498 cases; 8.47%). Pantoprazole reported palpitations (893 cases; 27.43%), tachycardia (332 cases; 10.20%), and cardiac flutter (326 cases; 10.01%), while lansoprazole (1,782 cases; 11.7%) reported palpitations (451 cases; 25.3%), tachycardia (166 cases; 9.3%), and cardiac flutter (153 cases; 8.6%). Esomeprazole was most associated with myocardial infarction (951 cases; 21.88%), palpitations (621 cases; 14.29%), and cardiac failure congestive (380 cases; 8.74%). PPIs are associated with cardiovascular ADRs such as palpitations and myocardial infarction, emphasizing the importance of careful risk assessment during therapy.